Is the management evaluation system of state-owned enterprises in the Republic of Korea a good tool for better performance? - Jhungsoo Park; Jina Kim; Chul Ju Kim (Asian Development Bank Institute (ADBI), 2019)
Based on the need for balance between autonomy and accountability in the management model of public institutions, an active discussion is needed for improvement of the evaluation system. A comprehensive control structure for better performance needs a smart evaluation system. However, from the perspective of the Organisation for Economic Co-operation and Development (OECD)'s guidelines for reforming the governance of state-owned enterprises (SOEs), comprehensive approval of the specific interference and influence of government concerning the operation of individual SOEs has many problems. Therefore, it is important to look for the balance point between standardization and customization. Ruminating on the Republic of Korea's SOE evaluation system with its 35-year history gives us many insights. Through historical institutionalism, we have learned that proper harmonization between structural reform on the hardware side and improvement of the program on the software side is extremely important, and it can be stably integrated into a systematic monitoring system. In accordance with that, it is necessary to design reform that takes into consideration the characteristics of individual institutions such as ownership structure, marketability, public interest, the size of the institution, etc., and to enhance the evaluation system for effective implementation. Every time a new administration emerges, privatization, structural reform, and the coordination of functions are essential processes to adapt to changes in the environment, and such improvement in the evaluation system of SOEs in the Republic of Korea so far shows moderate results. The fact that one system survived 35 years in the dynamic Republic of Korea proves it.
Keywords: L30; 330; state-owned enterprises; SOEs; quasi-governmental organizations; QGOs; performance evaluation; Republic of Korea; policy tool